Existence of Classical Solutions for a Class Nonlinear Wave Equations (Global Journal of Science Frontier Research, 2012)
In this article we investigate the Cauchy problem for the equation At this moment, the cases are well studied. open problem using approach.
Keywords: wave equation; existence